The Effectiveness of Instagram Account @fwidayantogallery in Attracting Tourist Visits to F. Widayanto Ceramic House Using the AIDA Model Approach - Alfia Prastiana, Lauditta; Erfinda, Yosi; Nurhidayati, Hindun (Journal of Digital Marketing and Communication, 2023)
Social media platforms, especially Instagram, played a strong role in promoting tourist attractions. F. Widayanto ceramic house was one of the tourist attractions that used Instagram as a place to market ceramic products and ceramic educational tours. The location of this study was at F. Widayanto ceramic house, Depok City, West Java. The manager of Keramik F. Widayanto ceramic house hoped that social media would be used as a media campaign to attract visits. This research was carried out by analyzing the interest of tourist visits to F. Widayanto ceramic house and analyzing the effectiveness of the @fwidayantogallery Instagram account in attracting tourists' visits using the AIDA model (attention, interest, desire, and action). The methods used were quantitative descriptive approaches and multiple linear regression analysis techniques. The number of respondents was obtained as many as 50 people from active users of Instagram. The results showed that the interest in tourist visits to F. Widayanto ceramic house, which obtained the highest score, was found in the component of the interested section to find information about the product, followed by finding out the product, considering buying, and being interested in trying. Meanwhile, the lowest value was found in the component of wanting to have. Based on the results of multiple regression analysis, the effectiveness of Instagram accounts using the AIDA Model consisting of the variables of attention, interest, desire, and action simultaneously had a significant effect on the interest of tourist visits to F. Widayanto ceramic house. Meanwhile, only the variables of desire and action had a significant effect on the interest of tourist visits partially.